Maker’s inventory system: a logical-bin storage approach - Teoh, Chia Yi (2020)
This project is an inventory system which is built especially for the makers. Makers often like to develop thing creatively by themselves and have many equipment or tools with them. Therefore, this system has come to help the makers to store their items. Normally, an inventory system used to keep every items accordingly which we called this technique as static slotting. However, the drawback of this method is to require many containers to store the items. Container acts as the storage for the item. Every items are categorized and store in the container according to their types. When a new type of item shows up, the makers have to add a new container to save the item. As a result, the containers will use up the physical spaces in order to place them. For this maker’s inventory system, the system will optimize all available spaces and use dynamic slotting method inspired by the Amazon’s chaotic storage approach. The makers can place any items in any containers without concerning the types of the items. This can decrease the amount of containers needed and saves spaces. The makers can manage this inventory system by performing Create, Retrieve, Update and Delete (CRUD) operations on each items and containers. The makers can also create and print out new barcode for the items and containers. Once the makers scan the barcode on the item using this system, they are able to locate which container has the respective item that they wanted to access. Similarly, the makers manage to find out all the items in the respective container by scanning the barcode on the container without the need of searching the containers one by one to look for the item. The makers can always check on the status of each items, for an example, the quantity of the items. They can decide when to restock. This inventory system also provides the feature for stock checking for makers.